Strategi Inovatif Kepala Sekolah: Manisan Buah Lipah sebagai Media Pembelajaran Kontekstual di SD Negeri 12 Samudera: Penelitian - Sarwadi; Iis Marsithah; Nurhafdar; Ainal Mardhiah; Irwati; Sahara (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In the midst of rapid globalization, preserving local cultural values has become urgent in the world of education. This study aims to describe the principal's innovative strategy in local wisdom-based contextual learning through lipah fruit candy as a learning medium at SD Negeri 12 Samudera, North Aceh. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The results showed that the principal implemented five main strategies: project-based curriculum application, collaboration with the local community, providing creative space for students, exhibitions and product marketing, and basic entrepreneurial training. This program positively impacts students' creativity, critical thinking skills, learning motivation, and nurtures entrepreneurial spirit. These findings serve as a reference for other schools to develop meaningful local wisdom-based education.